Pemerolehan bahasa verbal dan bahasa bukan verbal dalam kalangan kanak-kanak sindrom Down (Jurnal Bahasa, 2008)
This article describes the verbal and nonverbal language acquisition by Down syndrome children. Children with Down syndrome have difficulty processing and remembering verbal information. Learning to communicate using language has an impact on all areas of development including social and emotional development, and cognitive abilities. We use words for knowledge, thinking, reasoning, remembering and communicating with the world around us. There are two types of language acquisition, first using words (expressive language) and second, understanding words (receptive language). The research also indicates that children with Down syndrome are visual learner rather auditory learners. Due to that, the development of verbal language skills is usually supported by the use of nonverbal language such as gestures, signs, pictures, posture, etc.